2017
DOI: 10.1167/iovs.16-20043
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Patterns Involved in Amyloid Beta–Induced Retinal Degeneration

Abstract: Citation: Huang P, Sun J, Wang F, et al. MicroRNA expression patterns involved in amyloid beta-induced retinal degeneration. Invest Ophthalmol Vis Sci. 2017;58:172658: -173558: . DOI: 10.1167 PURPOSE. Dry age-related macular degeneration (AMD) is characterized by the accumulation of drusen under Bruch's membrane, and amyloid beta (Ab) is speculated to be one of the key pathologic factors. While the detrimental effects of Ab on retinas have been widely explored, Ab-induced epigenetic regulatory changes have ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…Our prior study showed that RPE cells from A β 1-40 -injected mice displayed hyper- and hypopigmentation. 21 In the current study, the structure and function of the retina were evaluated by TEM and ERG, respectively. The ultrastructural alterations and decreased ERG responses observed in our study were similar to those reported in other AMD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior study showed that RPE cells from A β 1-40 -injected mice displayed hyper- and hypopigmentation. 21 In the current study, the structure and function of the retina were evaluated by TEM and ERG, respectively. The ultrastructural alterations and decreased ERG responses observed in our study were similar to those reported in other AMD animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Human AMD samples displayed signi cant inter-individual variation in RPE transcript expression [5], supporting that heterogenic stress responses underlie AMD pathological process. C57BL/6 mice intravitreally injected with Amyloid-β 1−40 (Aβ 1−40 ) showed degenerative changes and apoptosis within the retina, and microRNAs (mi-RNAs) expression pro ling proved differential expression of miRNAs between the Aβ model and the control group [6]. However, these ndings cannot fully explain the data obtained from other researches.…”
Section: Introductionmentioning
confidence: 94%
“…Haematoxylin and eosin-stained sections of retinal pigment epithelium (RPE)/neural retina tissue of C57BL/6 mice intravitreally injected with Ab1-40 or PBS showed degenerative changes, and immunofluorescence testing demonstrated apoptosis within the retina after Ab1-40 injection [96]. In the same study, miRNA expression profiling proved differential expression of miRNAs between the Ab model and the control group.…”
Section: Micro-rnas and Post-transcriptional Modulation In Amdmentioning
confidence: 71%